Peran UN Women terhadap Gender-Based Violence di India: Studi Kasus Perempuan Kasta Dalit 2016-2018 - Pipin Indra Rohmawati; Satria Rizaldi Alchatib; Setyasih Harini (Program Studi Hubungan Internasional FISIP Universitas Jayabaya, 2023)
Cases of GBV (gender based violence) against women in India are an extreme manifestation of gender injustice targeting women and girls in the form of psychological, physical or sexual abuse. These manifestations of violence are rooted in various forms of discrimination and inequality faced by women. Apart from that, social norms such as patriarchy also cause Dalit women to become targets or victims of violence. Patriarchy basically encourages or justifies men to commit violence against women. The purpose of this study is to find out the role of UN WOMEN in the field of empowering women and children or gender equality, in the GBV (Gender Based Violence) Case in India with case studies of Dalit caste women in the 2016-2018 period. In this study, researchers used descriptive qualitative research methods. Research that uncovers social situations, does not use statistics, but data collection is analysis. UN Women plays a role in addressing inequality, and building resilience, by undertaking UN-Women's ongoing efforts to strengthen women's institutions, leadership and strategic interventions, to ensure that the voices of Dalit (Scheduled Castes), Ethnic (Scheduled Tribes) and religious minorities are heard and reflected in policy making. UN Women also plays a role and supports the formation of women's empowerment groups called Jugnu Clubs, in all tea plantations in Assam with the aim of preventing violence against women.